The Role of Notaries in the Auction Process: A Comparative Analysis be-tween Indonesia and Malaysia - Ummi Maskanah; Adinda Amalia Putri; Rizki Daffa Abiyyu; Zahra Ardhanie Praidno (IHSA Institute, 2025)
This study aims to analyse and compare the role of notaries in the auction process between Indonesia and Malaysia using a normative-comparative legal approach. The main issue of this study stems from the differences in institutional structure and legal basis governing the authority of notaries in the auction system in both countries. In Indonesia, the role of notaries is based on Law Number 2 of 2014 concerning the Position of Notaries, the Vendu Reglement (Staatsblad 1908:189), Minister of Finance Regulation No. 213/PMK.06/2020, and Minister of Finance Regulation No. 86/PMK.06/2024 concerning Auction Minutes. In Malaysia, auctions are conducted based on the National Land Code (Revised 2020) and Court Regulations 2012, which are carried out digitally through the e-Lelong system under the supervision of the High Court of Malaya. This study uses a normative-comparative legal approach (doctrinal and comparative legal research) with qualitative-descriptive analysis methods. The data used consists of secondary legal materials in the form of legislation, legal doctrine, and relevant academic literature. The analysis was conducted with reference to the theory of legal effectiveness (Fuller, 1969), the theory of legal certainty (Radbruch, 2006), and the theory of comparative legal functionalism (Zweigert & Kötz, 1998). The results of the study show that the Indonesian legal system is still centred on notaries, emphasising formal legitimacy and the authenticity of deeds, while Malaysia has implemented a judicial auction system model that integrates digitalisation and efficiency of legal processes through e-Lelong. The role of notaries in Indonesia is functional but limited, as the substantive authority to conduct auctions remains in the hands of auction officials, whereas in Malaysia, the function of notaries is almost non-existent as the entire process is under the control of the courts. Theoretically, this study reinforces the view that the effectiveness of the law is not determined solely by legal officials, but rather by the clarity of norms, institutional consistency, and the ability of the system to adapt to legal technology. In practical terms, this study recommends two things: (1) the need to harmonise regulations between the Notary Law and the Minister of Finance Regulation on Auctions to clarify the limits of legal officials' authority, and (2) the acceleration of national auction digitalisation, such as the e-Lelong system in Malaysia. Thus, Indonesia can realise a more efficient and transparent auction system that is in line with the principles of legal certainty, justice, and legal benefits.